Men’s Success in Higher Education: Model Building - Karie A Coffman PhD; Catherine H. Monaghan Ph.D. (Adult Education Research Conference, 2019)
This research addressed degree completion among adult male students. Findings illustrated that persistence depended on grit and a campus community where they could contribute and receive support to graduate.
Keywords: Undergraduate Education; Adult Education; and Qualitative Study